The Influence of Unemployment, Human Development Index and Gross Domestic Product on Poverty level - Dahliah, D.; Nirwana Nur, Andi (Manunggal Halim Jaya, 2021)
study was conducted with the aim of analyzing the effect of unemployment on the poverty level, the effect of the human development index (HDI) on the poverty level, gross domestic product (GDP) on the poverty level, and the effect of unemployment, HDI and GDP on the level of poverty. This study uses secondary data obtained from the Central Statistics Agency (BPS) and other related sources. Data were analyzed using the multiple linear regression model using SPSS 25 Application. The results of this study indicate that: (1) Unemployment has a positive and insignificant effect on the level of poverty; (2) Partially, the HDI and GDP have a negative and insignificant effect on the level of poverty; (3) Simultaneously Unemployment, HDI and GDP have a significant effect on the level of poverty. The results of this study indicate that in order to significantly reduce the Poverty Level in East Luwu, the three independent variables must be the attention of the East Luwu Government in making development policies. Increase the HDI mainly in terms of education and health to provide more competitive human resources, pursue high GDP growth level, and be more qualified and inclusive to reduce poverty levels in East Luwu.